Morphometric study of banded gourami (Colisa fasciata) in Jessore, Bangladesh (Asian Journal of Medical and Biological Research, 2016)
Population morphometry including population demography, size group distribution, length weight relationship and sex ratio of an important freshwater fish, Colisafasciata was studied which collected fromJessore and Jhenaidah districts in Bangladesh during May, 2014 to April, 2015. Random samples of 201 individuals (108males and 93 females) were collected from different fish markets in Jessore (Monirampur, Borobazar, Chowgasa) and Jhenaidah (Mohespur, Barobazar, Kotchandpur) districst. The mean size of the specimen was recorded 65.08 ±14.32 mm in length and 7.43 ±3.09 g in body weight. Females were found little smaller than males. The specimens were larger in winter than summer and monsoon season. But in monsoon season the females were larger than males. The maximum length of the specimen collected from Jhenaidah district was smaller compare to the specimen of Jessore district. Most of the population (29%) was observed under 55-64 mm size class. Linear relationship was obtained between the log length (mm) and log weight (g) of the species in respects of sexes, seasons, and districts. The allometric coefficient b of the relationship indicated negative allometric growth of the species as b value was less than 3. The overall sex ratio (male: female=1:0.86)showed significant difference from the expected value 1:1. Overall males showed non-significant over females (?2 =1.119) in all season of both districts but in November males showed the significant (P